Design and analysis of triple-band microstrip patch antenna with h-shaped slots - Noori, Omar; Chebil, Jalel; Habaebi, Mohamed Hadi; Islam, Md. Rafiqul; Saeed, Rashid Abdelhaleem (IEEE, 2012)
Multi-band antennas are very important in many application systems such as mobile phone jammer. A new shape triple-band microstrip antenna is proposed in this paper. By embedding h-shaped slots placed in the centre of a microstrip patch, the triple-band character can be achieved. Procedures to select the length and location of the h-shaped slots were discussed in detail. The required antenna gain, input impedance, radiation pattern and return losses were achieved.